SISTEM INFORMASI MANAJEMEN TERHADAP EFEKTIVITAS KERJA PEGAWAI YAYASAN PENDIDIKAN TELKOM BANDUNG - Vidya Triocssy Nurrani; Ary Ferdian (Faculty of Economic and Business, University of Pasundan, 2018)
This study aims to determine the effect of management information systems by specializing memo online information system on the effectiveness of employee on YPT Bandung. This research was based on the theory of management information system and work effectiveness by McLeod and Notoatmodjo. This research uses quantitative method with sample of 64 people using census sample technique. The research shows that the management information system has an influence on the employee effectiveness of Yayasan Pendidikan Telkom Bandung of 28.1%. The company should listen to complaints from employees of the memo online information system and improve in accordance with the expected by the employee, upgrade to memo online ver 3.0 conduct motivational seminars for employees.